The Application of Parenting Cooperation Between Parents and Teachers in an Effort to Maintain the Physical Fitness of Deaf Children - Luthfie Lufthansa; Ary Artanty; Laila Nur Rohmah; Pinton Setya Mustafa; Ismail Gani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the application of parenting cooperation between parents and teachers in an effort to maintain the physical fitness of deaf children in Special Elementary Schools. The method used is qualitative research with a case study approach. Qualitative research methods with data collection techniques of interviews, observation, and documentation allow researchers to obtain comprehensive and in-depth data on how parenting patterns and the role of teachers collaborate in maintaining the physical fitness of deaf children in Special Elementary Schools. The research sample used was 3 physical education teachers who taught at different Special Elementary Schools and 6 parents who had deaf children. The data collected were then analyzed interactively through data reduction, data presentation, and conclusion drawing. The results showed that effective cooperation between parents and teachers, in the form of regular communication, joint physical exercise program preparation, as well as consistent emotional support and motivation, contributed significantly to improving the physical fitness of deaf children. Obstacles encountered include parents’ limited time, lack of knowledge, and suboptimal communication, but can be overcome with training and facilitation from the school. In conclusion, the synergy of parents’ parenting and adaptive teachers’ roles is crucial in supporting the physical health and development of deaf children in Special Elementary Schools.